HISTO-MORPHOMETRIC COMPARSION STUDY OF THE COLON IN SHEEP AND GOAT IN SOUTH IRAQ. - Eyhab R. M. AL-Samawy; Diyar M.H. Kadhim; Dina Hamid Sadiq; Israa Jawad; Ihab Abbas Taher (Basrah Journal of Veterinary Research)
In the present study, the histo-morphometric comparison study of colon in goat and sheep wasaimed. Ten of clinically healthy sheep and goats of both sexes were collected by Al-Simawaabattoir, age ranged between 2 to 3 years, which was estimated according to the dental equationof the animals. The colon was cut and stained alternatively with Hematoxylin and Eosin (H & E)and (PAS).The epithelium was simple tall columnar epithelia that has goblet cells, these epithelia lining thefolds of mucosa . In sheep the folds characters by a large number of goblet cells and the foldappeared long leaf-shaped folds arranged in a zig-zag pattern , whereas, in goat appeared shortand blunt. The submucosa of the colon in the animals composed of abundant, dense connectivetissue containing blood vessels and nerves. The muscularis externia composed of a thin, outerlongitudinal layer and a thick inner circular layer between this was a narrow connective tissue.Externally, there was coated with layer of simple squamous epithelium under which was a thinlayer of loose connective tissue containing a few small elastic fibers.